SIPKOM: Efektivitas Sistem Perkuliahan di JTIK Universitas Negeri Makassar Berbasis Website - Achyar AM, Andi Muh; Rauf, Annajmi; Sirenden, Deswanto Richard; Faruq, Ahmad Faris Al; Tabagas, Nor Ihsan (Journal of Security, Computer, Information, Embedded, Network, and Intelligence System, 2023)
This research aims to implement an announcement and communication information system in the Department of Informatics and Computer Engineering, Universitas Negeri Makassar. The system utilizes information technology that combines computation and interaction to develop software and hardware components. Prior to the existence of e-learning, learning was conducted face-to-face, but having these two learning options could lead to communication gaps between teachers and students. Therefore, a website-based announcement and communication information system (SIPKOM) was developed to provide quick information and enable communication among students, administrators, and teachers. The research and development method was employed in this study. Data was collected through literature review, scientific journals, and online questionnaire distribution using Google Form. The system development utilized Agile Development methodology, allowing for quick adaptation to changes. The system design was based on Unified Modeling Language (UML) for visualization and design standards. System testing was conducted through Black box testing, where software was tested without considering its internal details. The development plan for the SIPKOM application encompassed Use case modeling, Activity diagram, sequence diagram, and class diagram. Use case modeling was used to represent the interactions between users and the system. The Activity diagram was utilized to depict the workflow of the application, including schedule display, account announcements, and chat features. Through this research, it is expected to provide a comprehensive insight into the effectiveness of the announcement and communication information system in the Department of Informatics and Computer Engineering. The system is anticipated to help overcome communication gaps between teachers and students and enhance the efficiency of information management and communication in the academic environment.